Zweiter Abschnitt der Antarktis -Expedition 1977/78 beendet - Hempel, Gotthilf; Freytag, G. (1978)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010